Evaluation of the Pattern of Prescribing Antimalaria Drugs - Farhan Imba; Nawang Wulan Nago Pita Sari; Ferdinta D Setyawan; Risna Risna; Gabriela Welma Litaay (GLOBAL HEALTH SCIENCE GROUP, 2026)
Malaria is caused by infection with the plasmodium virus that comes from the Anopheles mosquito. This disease often occurs in the rainy season and can cause morbidity and even death for humans. Based on data from the Ministry of Health, there were 304,607 cases of 247 malaria in Indonesia throughout 2021, this figure increased by 19.9% compared to the previous year of 254,050 cases, Papua is the province with the most cases. The highest number of malaria cases in Indonesia in 2021 was recorded at 275 cases. Objective: determine the pattern of prescribing anti-malaria drugs at the Sentani Health Center (period October-December 2023). Method: quantitative descriptive type. it is an evaluation of the pattern of prescribing antimalarial drugs at the Sentani Health Center for the period October-December 2023 with a sample of 33 prescriptions carried out in October-December 2023 using a technique, namely purposive sampling the Data was obtained using Excel and the processing was analyzed. Result: evaluation of the pattern of prescribing antimalarial drugs at the Sentani Health Center for the period October-December 2023. The highest prevalence of antimalarial drug use in Sentani Health Center in Jayapura regency is DHP (Dihydroartemisinin-Piperaquine) with a percentage of 100%.